Influence of Photon Beam and Motor Vibrations on At-Wavelength X-Ray Speckle Scanning Metrology - Tian, Naxi; Jiang, Hui; Xue, Lian; Xie, Jianan (Frontiers in Physics, 2022)
Speckle scanning metrology is a strong tool to determine the X-ray wavefront error in synchrotron radiation. By measuring wavefront radii of curvature , X-ray optics can be high-precision aligned and adaptive optics can be used to compensate these wavefront errors to pursue an aberration-free wavefront. Photon beam and motor vibrations are the major limits in characterizing the beam performances. An analytical model is presented in this article to reveal the influences of photon beam and motor vibrations on the measurements of the wavefront radii of curvature. It is worth noting that the influence of low-frequency vibration is oscillatory, so that the selection of sampling frequency is strongly related. The experimental results verify the model and reveal the main dependency of the experimental deviations on the amplitude and frequency of vibrations.